The Identification of Religious Character Values on Serenade Senja - Dian Tri Riska Ekawati; Mutmainnah Mustofa; Saiyidi Hasbullah (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
This study aimed at identifying the religious character values and to describe them presented by the main figures in Serenade Senja. It was conducted by qualitative research. The procedure of the research was reading the book repeatedly, focusing on religious values explained in the book, adding some references relevant to this study, and searching various sources to analyze the data. The religious values were found in three short stories namely KepunyaanMu, Kertas Kusam, and Serenade Senja. The characters of this story were described as religious characters. They did the worship diligently, remembered Allah anytime, kept promises, respected and supported others, being sincere, respectful, friendly, and grateful in their life. Those characters could be analyzed from the various part of the story. It could be concluded that literature becomes a media to convey the message which is available in the story to make the reader gaining the benefit and actualizing in real-life so that the life becomes better life in the next future.